BRAIN CHANGER. Felice Jacka, 321 pages, Macmillan, 2019 (ISBN: 978-1-76055-651-8) - Cécil J.W. Meulenberg (Exercise and Quality of Life)
This easy readible and thoroughly scientifically-backed book by australian professor Felica Jacka, explains the recent science on how diet can affect the brain and mental health, with a specific focus on the risk to anxiety and depression. The scientific evidence is drawn from the results with larger cohorts and randomized controlled trials including amongst others: ALSPAC (Avon Longitudinal Study of Parents and Children, United Kingdom); HELFIMED (Healthy Eating for Life with a Mediterranean Diet, Australia); HUSK (Hordaland Health Study, Norway); PREDIMED (Prevencíon con Dieta Mediterránea, Spain); SMILES (Supporting the Modification of Lifestyles in Lowered Emotional States, Australia). These and other studies show that wherever the geographical area, plant-based Mediterranean-like diets improve the health outcomes of children, adolescents, adults and ageing individuals affected by mental health illnesses, in cost-effective ways. Consecutive chapters illustrate recent understandings of the effects of diets on the immune system, their influence on brain plasticity (which also occurs in older humans), epigenetics, food sensitivities, inflammation, and centrally, the importance of food to the gut microbiota (including the consumption of fermented foods). These effects are explained simply and efficiently in relation to mental health, as well as briefly to psychotic illnesses, autism and ADHD. By doing so, it is possible for every physical-activity researcher or athlete interested in the combination of nutrition, lifestyles and good habits, to get up to date easily, or to make a first aquaintance with the fields of nutrition and brain health. The appendix contains a reference list that restricts itself to the most influential studies like systematic reviews and meta-analysis. Also included is the Modified Mediterranean Diet (ModiMED) food pyramid, and several ModiMEd recipies (used in the SMILES study), as well a weekly meal planner, that all could be of use to get started with an easy intervention study. Although it is intended for the general public, the book is recommended for scholars of any life sciences. With her to-the-point and easy language writing gift, professor Jacka manages to explain the complicated matters of brain health effortlessly. She does this convincingly, but not superficially, relevant and correct, without any simplification. To influence mental health through nutritious, whole foods will be an essential topic to come, also in the fields of sports. In that sense Brain Changer, can be exactly that.